Implementing Validated UI/UX Design into a Real System: An Agile Kanban-Based Development Evaluation in an Educational Information System - Indah Lestari; M. Fakhri Salman; Anggy Trisnadoli; Muhammad Mahrus Zain (Center for Research and Community Service, Institut Informatika Indonesia (IKADO) Surabaya, 2026)
UI/UX research often ends at the prototype validation, while the implementation process remains limited in empirical studies. This study implements UI/UX designs validated in previous research into an information system and evaluates the role of the Agile Kanban approach in bridging the gap between design and real system implementation. The research method uses an implementation-based evaluation that includes system requirements alignment, Agile Kanban-based iterative development, and post-implementation evaluation. The results show that of the total 34 screens developed, 6 were implemented according to the initial design, 8 were adjusted during development, and 20 additional screens were developed to meet operational stakeholder needs. Development performance reached 135%, calculated as the ratio between completed and initially planned features. The development process was conducted through 4 Kanban cycles that allowed for controlled adjustments to business logic and feature additions. This study identified 5 main gaps in the implementation of the design in the real system. Post-implementation evaluation showed that all 79 functional requirements were successfully implemented with a total of 27 functional features, exceeding the initial plan of 20 features. The system was declared fully accepted through User Acceptance Testing and achieved a System Usability Scale score of 78.3 from 60 respondents, which is in the Acceptable category. These results indicate that Agile Kanban is effective in bridging the gap between UI/UX design validation and real system implementation, and is able to maintain usability quality in operational systems. This provides practical direction for organisations that seek to operationalise validated designs within dynamic development settings.